Digitize and punish : racial criminalization in the digital age - Jefferson, Brian Jordan, 1981- (University of Minnesota Press, 2020)
"Brian Jefferson explores the history of digital computing and criminal justice, revealing how big tech, computer scientists, university researchers, and state actors have digitized carceral governance over the past forty years."--